Penerapan Manajemen Risiko IT pada Bank X dengan Menggunakan Framework COBIT 2019 - William Jordy; Leo Willyanto Santoso; Yulia Yulia (Universitas Kristen Petra, 2022)
At Bank X, various problems occurred in business processes involving IT. problems occur such as unstable server network conditions and experiencing problems when carrying out business processes inputting data. The purpose of this thesis is to find out what factors or causes are the most influential in the use of IT in Bank X's business processes and provide a response to existing risks based on the 2019 CobiT guidelines with the Align, Plan and Organize (APO) domain in the APO 11 Managed Quality process. and APO 12 Managed Risk. Methodology The research will be conducted by examining the capability level and conducting a risk assessment using the OWASP standard in the APO11 and APO12 domains in accordance with the results in the Mapping Alignment Goal (AG) and Enterprise Goal (EG) as well as the BSC dimensions. Based on the results of research conducted, the authors found several risks that have an impact on the company's IT business processes along with the responses and solutions provided. The solution given is to Mitigate or Avoid depending on the risk severity of the risks. The conclusion of this research is that the IT Division has an important role in running the company's business processes. In addition to acting as support, the IT division also has a role in software development in customer banking applications, respondent transparency and the IT division as the company's support system are important factors in assisting this research.